The Effect of Phase-Feeding Strategies on Growth Performance and Carcass Characteristics of Growing-Finishing Pigs: II. Field Approach on Lysine Levels - M. B. Menegat; S. S. Dritz; M. D. Tokach; J. C. Woodworth; J. M. DeRouchey; R. D. Goodband (Kansas Agricultural Experiment Station Research Reports, 2018)
The objective of this study was to evaluate phase-feeding strategies for grow-finish pigs under commercial research conditions and using a field approach with lysine levels slightly below the pig’s requirement estimates for maximum growth performance. A total of 1,100 pigs (PIC 359 × 1050; initially 57 lb body weight (BW)) were used in a randomized complete block design with 25 pigs per pen and 11 pens per treatment. Treatments consisted of four feeding programs: a 1-phase feeding program with 0.79% standardized ileal digestible (SID) lysine from 60 to 280 lb BW; a 2-phase feeding program with 0.91 and 0.72% SID lysine from 60 to 220 and 220 to 280 lb BW, respectively; a 3-phase feeding program with 1.07, 0.85, and 0.72% SID lysine from 60 to 110, 110 to 220, and 220 to 280 lb BW, respectively; and a 4-phase feeding program with 1.07, 0.91, 0.79, and 0.72% SID lysine from 60 to 110, 110 to 160, 160 to 220, and 220 to 280 lb, respectively. The lysine levels were determined based on the estimated lysine requirements to achieve 98.5% of maximum growth rate for the weight range in each phase, using an equation developed by the genetic supplier. The experimental diets were based on corn, distillers dried grains with solubles (DDGS), and soybean meal. Overall, from d 0 to 119, pigs fed the 1-phase feeding program had decreased (P= 0.009) average daily gain (ADG) compared to those fed the 4-phase feeding program, with 2- and 3-phase feeding programs intermediate. The 1-, 2-, and 3-phase feeding programs resulted in poorer (P<0.001) feed efficiency (F/G) compared to the 4-phase feeding program, with the poorest F/G observed in pigs fed the 1-phase feeding program. Final BW and hot carcass weight (HCW) were lower (P<0.05) in pigs fed the 1-phase program compared to the 4-phase program, with 2- and 3-phase programs intermediate. No evidence for differences was observed across the feeding programs for average daily feed intake (ADFI), carcass yield, backfat thickness, loin depth, or percentage lean. For economics, income over feed costs (IOFC) per pig was increased (P= 0.018) in the 4-phase program compared to the 1-phase program, with the 2- and 3-phase feeding programs intermediate. In conclusion, phase-feeding strategies provide advantages in growth performance and economics over feeding a single diet throughout the grow-finish phase. Moreover, simplification of feeding programs to two or three dietary phases with lysine levels slightly below the requirement estimates (98.5% of maximum growth rate) have negative implications on overall feed efficiency compared to a feeding program with four dietary phases.
Keywords: compensatory growth; feeding regimen; finisher; nutrition; swine